Pengelolaan Aset Desa di Kabupaten Tangerang - Firmansyah, Amrie (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
This study aims to determine the administration of village assets. The method used is descriptive qualitative research method and using data research technique with in-depth interview, observation and documentation. The selection of Rawa Burung Village and Rawa Rengas Village in this study because the two villages have a location close to DKI Jakarta Province which is expected to have competent employees in the management of village assets. Yet, there have not been party that handles specific assets in both villages. The sources of information in this research are the head of planning affairs of rawa rengas village and head of the regional government section, whose field of work is not related to the management of the village assets directly.The results of this study conclude that the administration of village assets has not been done optimally, especially in Rawa Rengas Village which has not been implemented village assets reporting, thus it has not been implemented accountably and transparently. The management of village assets, especially its administration, is focused on one party only, whereas for the job it requires a sufficient number of employees with competency in the administration of the assets. In addition, village accounting standards included in the setting up of village assets is still existed due to the limitations of government accounting standards which only regulate accounting of central government and local government assets.